2020
DOI: 10.1590/1678-9199-jvatitd-2020-0025
|View full text |Cite|
|
Sign up to set email alerts
|

Streamlined downstream process for efficient and sustainable (Fab')2 antivenom preparation

Abstract: Background: Antivenoms are the only validated treatment against snakebite envenoming. Numerous drawbacks pertaining to their availability, safety and efficacy are becoming increasingly evident due to low sustainability of current productions. Technological innovation of procedures generating therapeutics of higher purity and better physicochemical characteristics at acceptable cost is necessary. The objective was to develop at laboratory scale a compact, feasible and economically viable platform f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In an analysis of different antivenom lots produced by the Butantan and Vital Brazil Institutes, bands of similar weights were identified as protein contaminants unrelated to degradation products of IgGs [ 34 ]. However, a different study concluded that bands smaller than 20 kDa in experimental antivenoms represent residues from the digestion of the heavy chain of IgGs and inter-alpha-trypsin inhibitors [ 35 ]. These reports emphasize the need for further assays to fully identify the bands migrating below 20 kDa in antivenoms produced by Birmex.…”
Section: Resultsmentioning
confidence: 99%
“…In an analysis of different antivenom lots produced by the Butantan and Vital Brazil Institutes, bands of similar weights were identified as protein contaminants unrelated to degradation products of IgGs [ 34 ]. However, a different study concluded that bands smaller than 20 kDa in experimental antivenoms represent residues from the digestion of the heavy chain of IgGs and inter-alpha-trypsin inhibitors [ 35 ]. These reports emphasize the need for further assays to fully identify the bands migrating below 20 kDa in antivenoms produced by Birmex.…”
Section: Resultsmentioning
confidence: 99%
“…Administration of antivenom is considered the sole effective and accepted treatment for snake envenomation (14,15). Despite the long precedence of antivenom production, there are various problems in different manufacturing processes and some efforts are being made in manufacturing protocol to improvement the antivenom production (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Pure IgGs are extracted from pooled plasma collected from convalescent donors by sequence of different fractionation steps, among which the most widely used are precipitation and liquid chromatography [ 5 , 6 , 7 , 8 , 9 , 10 ]. Caprylic (octanoic) acid (CA) as a fractionation agent is frequently used to purify IgGs from both animal [ 11 , 12 , 13 ] and human plasma [ 4 , 14 , 15 , 16 , 17 ], particularly in recent developments of SARS-CoV-2 specific immunoglobulin preparations [ 4 , 18 , 19 ]. CA selectively precipitates non-immunoglobulin proteins without affecting IgGs, which remain in solution, preserving their structural and conformational stability [ 6 , 7 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%